Pengaruh Resiliensi terhadap Job Insecurity pada Pegawai Honorer - Zakaria, Mochamad Amin; Hasanti, Nida; Shohib, Mohammad (Fakultas Psikologi, 2019)
The existence of honorary staff who cannot be appointed as permanent employees is one of the problems that have yet to be resolved. The honorary employees certainly want to get their rights as employees who work to devote themselves to the community. Employees who feel that job security is certainly less able to accept changes in the conditions of the work environment which would make them unable to develop in the work environment. Jobs that are not permanent will create job insecurity conditions. The attitude of employees in facing a change is, of course, different, employees with high resilience can be interpreted as being able to adapt and can change a chaotic environmental condition to solve problems and turn them towards a positive one. The purpose of this study is to see how much influence the resilience of job insecurity has on honorary employees. This research is quantitative research with the number of subjects 129 honorary employees. The method of data collection uses the Job Insecurity Quisionare scale and the CD-RISC scale. Data analysis using a linear regression test. The results showed that ß -0.252 p0,000 note that there was a negative effect on resilience towards job insecurity, which means that the higher the resilience, the lower the job insecurity. Resilience contributed significantly (9.3%) to job insecurity.